New P–T constraints on the Tamayen glaucophane‐bearing rocks, eastern Taiwan: Perple_X modelling results and geodynamic implications. (12th September 2016) - Baziotis, I.; Tsai, C.‐H.; Ernst, W. G.; Jahn, B.‐M.; Iizuka, Y.
Abstract: New pseudosection modelling was applied to better constrain the P–T conditions and evolution of glaucophane‐bearing rocks in the Tamayen block of the Yuli belt, recognized as the world's youngest known blueschist complex. Based on the predominant clinoamphibole, textural relationships, and mineral compositions, these glaucophane‐bearing high‐ P rocks can be divided into four types. We focused on the three containing garnet. The chief phase assemblages are (in decreasing mode): amphibole + quartz + epidote + garnet + chlorite + rutile/titanite (Type‐I), phengite + amphibole + quartz + garnet + chlorite + epidote + titanite + biotite + magnetite (Type‐II), and amphibole + quartz + albite + epidote + garnet + rutile + hematite + titanite (Type‐III). Amphibole exhibits compositional zoning from core to rim as follows: glaucophane → pargasitic amphibole → actinolite (Type‐I), barroisite → Mg‐katophorite/taramite → Fe‐glaucophane (Type‐II), glaucophane → winchite (Type‐III). Using petrographic data, mineral compositions and Perple_X modelling (pseudosections and superimposed isopleths), peak P–T conditions were determined as 13 ± 1 kbar and 550 ± 40 °C for Type‐I, 10.5 ± 0.5 kbar and 560 ± 30 °C for Type‐II (thermal peak) and 11 ± 1 kbar and 530 ± 30 °C for Type‐III. The calculations yield higher pressures and temperatures than previously thought; the difference is ~1–6 kbar and 50–200 °C. The three rock types record similar P–T retrograde paths with clockwise trajectories; all rocks followed trajectories with substantial pressure decrease under near‐isothermal conditions (Type‐I and Type‐III), with the probable exception of Type‐II where decompression followed colder geotherms. The P–T paths suggest a tectonic environment in which the rocks were exhumed from maximum depths of ~45 km within a subduction channel along a relative cold geothermal gradient of ~11–14 °C km −1 .